ANALISIS DAYA DUKUNG LAHAN KAWASAN PERMUKIMAN DI KECAMATAN LUWUK DAN LUWUK UTARA KABUPATEN BANGGAI - Andre P. Satolom; Sonny Tilaar; Roosje J. Poluan (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
The rapid development of settlements in Luwuk and North Luwuk Subdistricts has an impact on the physical condition of the land so that the demand for residential land needs increases. The purpose of this study is to analyze the carrying capacity of residential areas using the concept of building coverage and to analyze the direction of settlements based on the carrying capacity of residential areas in Luwuk and North Luwuk Districts. The research method used is descriptive quantitative, using a spatial analysis approach with the help of a Geographic Information System (GIS). In data analysis using technical guidelines for analysis of physical and environmental, economic and socio-cultural aspects in the preparation of spatial plans (Minister of Public Works Regulation No.20/PRT/M/2007). The analytical technique used is overlay and scoring analysis for assigning values to each parameter. The results of the analysis of the carrying capacity of residential areas in Luwuk and North Luwuk sub-districts are by establishing a protected area based on the physical condition of the environment. The direction of settlement development in Luwuk District for Class 1 is 20.16 Ha/48% land cover ratio, North Luwuk District 176.60 Ha/42% cover ratio. Class 2 in Luwuk District is 92.13 Ha/19% land cover ratio, North Luwuk District is 3588.01 Ha/50% cover ratio. Class 3 is 168.10 Ha/20% cover ratio, North Luwuk District 1866.62 Ha/20% cover ratio. and Class 4 Luwuk District 5080.15 Ha/0% cover ratio, North Luwuk District 23355.84 Ha/0% cover ratio.